Las tecnologías de la información y comunicación de la cadena de suministro y su impacto en la competitividad en el sector hotelero del estado de Michoacán - Béjar Tinoco, Víctor (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
This doctoral thesis aims to examine the technological tools of information and communication to improve the supply chain with suppliers and clients in hotel companies in Michoacán. Specifically, it aims to show the effects of Information and Communication Technologies (ICT) in the supply chain at an internal level, such as the interaction with suppliers and clients on the impact of Competitiveness in the hotel sector. The objective of this doctoral research was to determine to what extent the information and communication technologies in the administration, both in the relationship of suppliers, the internal supply chain, the relationship with customers affect competitiveness in the hotel sector. from the state of Michoacán. Therefore, this research presents a general model to be verified based on the study of the literature in relation to its ICT constructs in the administration in relation to the suppliers, ICT in the internal supply chain and ICT in the administration in relation to the customers in the supply chain. The competitiveness in the hotel sector stands out as theoretical support. The proposed theoretical model was configured from the review of the literature. Subsequently, an instrument was developed to measure the relationship of the constructs of the proposed theoretical model. To contrast the model, primary information was collected from a random, representative and proportional sample of 172 hotel companies from Michoacán registered AHMEMAC and in the National Tourism Registry (RNT). Following the scientific method, a causal empirical study is presented, and the information analysis technique was initially at a descriptive level (with the SPSS 25.0 software), and later the validity of the instrument was confirmed by means of the multivariate statistical technique of equations. partial least squares structures (PLAS-SEM for its acronym in English).

Esta tesis doctoral pretende examinar las herramientas tecnológicas de la información y comunicación para mejorar la cadena de suministro con proveedores y clientes en empresas hoteleras en Michoacán. Concretamente pretende mostrar los efectos de las Tecnologías de la Información y Comunicación (TIC) en la cadena de suministro a nivel interno como la interacción con proveedores y clientes en el impacto de la Competitividad en el sector hotelero. El objetivo de esta investigación doctoral fue: determinar en qué medida las tecnologías de la información y comunicación en la administración, tanto en la relación de los proveedores, la cadena de suministro interna, la relación con los clientes incide en la competitividad en el sector hotelero del estado de Michoacán. Por tanto, esta investigación se presenta un modelo general a comprobar basado en el estudio de la literatura en relación a sus constructos TIC en la administración con relación con los proveedores, TIC en la cadena de suministro interna y TIC en la administración con relación con los clientes en la cadena de suministro. Destaca la competitividad en el sector hotelero como sustento teórico. El modelo teórico propuesto se configuró a partir de la revisión de la literatura. Posteriormente se elaboró un instrumento para medir la relación de los constructos del modelo teórico propuesto. Para contrastar el modelo se recabó información primaria de una muestra aleatoria, representativa y proporcional de 172 empresas hoteleras de Michoacán registradas AHMEMAC y en el Registro Nacional de Turismo (RNT). Siguiendo el método científico, se presenta un estudio empírico causal, y la técnica de análisis de la información fue inicialmente a nivel descriptivo (con el software SPSS 25.0), y posteriormente se confirmó la validez del instrumento por medio de la técnica estadística multivariante de ecuaciones estructurales con mínimos cuadrados parciales (PLAS-SEM por sus siglas en inglés).
Facultad de Contaduría y Ciencias Administrativas. Doctorado en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-D-2023-0311; Cadena de suministro; Hoteles; Competitividad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16346